Administration of cinnamaldehyde promotes osteogenesis in ovariectomized rats and differentiation of osteoblast in vitro - Zongyi Wu; Sheji Weng; Deyi Yan; Zhongjie Xie; Qiang Zhou; Hang Li; Bingli Bai; Viraj Boodhun; Zijian Shen; Jiahao Tang; Lingling Zhou; Zhoushan Tao; et al. (Elsevier, 2018)
To explore the effect of cinnamaldehyde on the distal femur in ovariectomized rats and its influence on osteoblast in vitro. Female Sprague-Dawley rats which underwent either bilateral ovariectomy or sham operation were divided into five groups randomly: group OVX (OVX, N = 10) and group sham (SHAM, N = 10) received normal saline (NS) by gavage at a dose of 50 ml/kg·d; group low dose, group middle dose and group high dose received cinnamaldehyde by gavage at a dose of 25 mg/kg·d (OLD, N = 10), 50 mg/kg·d (OMD, N = 10), and 75 mg/kg·d (OHD, N = 10) respectively. Distal femurs were harvested for hematoxylin and eosin (HE) staining, micro-ct scanning and immunohistochemical analysis. Murine mesenchymal stem cells were cultured and dealt with the presence of either cinnamaldehyde at a dose of 15ug/ml (OLD), 30ug/ml (OMD), 60ug/ml (OHD) or vehicle. ALP staining and western blot were performed to observe the influence of cinnamaldehyde on the differentiation of osteoblast. HE and micro-ct results indicated that osteogenesis were promoted with the treatment of cinnamaldehyde. Immunohistochemical results showed that cinnamaldehyde increased the number of osteoblast and decreased the number of osteoclast. In vitro studies indicated that cinnamaldehyde promoted expression of alkaline phosphatase (ALP), runt-related transcription factor 2 (RUNX2), osteocalcin (OCN) and collagen type Iɑ1 (COL1ɑ1). The treatment effect behaved as dose-dependently. Thus, cinnamaldehyde inhibits osteoclastogenesis and promotes osteoblastogenesis, and may plays an important role in the treatment of osteoporosis clinically. Keywords: Cinnamaldehyde, Anti-Osteoporosis, Bone morphology, Osteoblast, Osteoclast